box.m - t=-5:0.1:5 box1 = boxt(t-1,1,0.1 subplot(3,1,1 plot(t,box1 t=-5:0.2:5 box2=boxt(t-1,1,0.2 subplot(3,1,2 plot(t,box2 t=-5:0.5:5

box.m - t=-5:0.1:5 box1 = boxt(t-1,1,0.1 subplot(3,1,1...

This preview shows page 1 out of 1 page.

t=-5:0.1:5; box1 = boxt(t,-1,1,0.1) subplot(3,1,1) plot(t,box1) t=-5:0.2:5; box2=boxt(t,-1,1,0.2) subplot(3,1,2)
Image of page 1

You've reached the end of your free preview.

Want to read the whole page?

  • Fall '19
  • dsadas

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture

Stuck? We have tutors online 24/7 who can help you get unstuck.
A+ icon
Ask Expert Tutors You can ask You can ask You can ask (will expire )
Answers in as fast as 15 minutes